Vindication of Newmans Views on Liberal Education from Contemporary Perspective - Alam, Mohammed Sarwar (IIUC Studies, 2012)
Through his provocative and evocative lectures at the Catholic University of Ireland, John Henry Cardinal Newman (1801-1890) appealed to incorporate liberal education in university education to form a better and sounder society. Endorsing Newmans views/thesis, this paper argues that colonially shaped, commercially motivated and morally bankrupt higher education system has strained liberal education to a large extent. And predictably, now we are perhaps experiencing an increasingly paradoxical scenario of an inhuman society by the human beings. In spite of predictable and unpredictable changes in social dynamics and paradigms since Newman expressed his views, this paper seeks to arrive at an understanding that his insightful defence of liberal education is still rewardingly relevant. DOI: http://dx.doi.org/10.3329/iiucs.v6i0.12249 IIUC Studies Vol.6 2010: 65-76